If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6x + -10 = 14 Reorder the terms: -10 + 2x + 6x = 14 Combine like terms: 2x + 6x = 8x -10 + 8x = 14 Solving -10 + 8x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 8x = 14 + 10 Combine like terms: -10 + 10 = 0 0 + 8x = 14 + 10 8x = 14 + 10 Combine like terms: 14 + 10 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| 8/9=12/p | | 12/5=n/8 | | 3ln(x)-4=0 | | 26x-17y=180 | | x-8=9.79 | | -8n+4=7n-3 | | z=-8+6i | | Y=cos3/2x | | 5x+25=8x+16 | | 5x+5=8x+2 | | 40/x-40/x-6=7/x | | 7x-28/5=2x | | 2(w-6)/9=2 | | 3f+7=-11 | | 8x+16=5x+15 | | 1/2ln2 | | x^2-4x=x+24 | | x-19/x-203 | | h(x)=3*-5+5 | | 6(j+434)=984 | | x^2+5x+5x+24=0 | | (3x-5)x=0 | | 19(r+954)=266 | | y=26-4*6 | | y=26-4*5 | | x+8=1008 | | r^2+10r+35=0 | | y=26-4*4 | | 7x-9=7(x-1)-2 | | 20/14=90/t | | y=26-4*2 | | T^2=4t+6 |